Geographies of obesity environmental understandings of the obesity epidemic - Pearce, Jamie; Witten, Karen (Farnham, Surrey, England Ashgate Publishing Limited, 2010)
Over the past two decades, rates of adult and childhood obesity in the developed world have risen sharply. By the year 2000, 65% of the United States population were overweight, 30% of these obese. Whilst medical treatment has tended to focus on individual habits of diet and exercise, this approach does little to account for globally increasing levels of obesity, and the external, environmental factors that may be responsible. This in-depth study assembles the evidence for a geographical explanation of current obesity trends, and is the first work to examine the ways in which environment and living conditions promote an imbalance of energy intake over energy expenditure. The book calls upon the expertise of geographers, nutritionists, epidemiologists, sociologists and public health researchers, resulting in a broad, multidisciplinary analysis of this important health issue.
Introduction : bringing a geographical perspective to understanding the 'obesity epidemic' / Jamie Pearce and Karen Witten -- The emerging obesity epidemic : an introduction / Barry M. Popkin -- Contextual determinants of obesity : an overview / Daniel Kim and Ichiro Kawachi -- Changing food environment and obesity : an overview / Janet Hoek and Rachael McLean -- Understanding the local food environment and obesity / Lukar E. Thornton and Anne M. Kavanagh -- Childhood obesity and the food environment / Mat Walton and Louise Signal -- The role of the changing built environment in shaping our shape / Billie Giles-Corti, Jennifer Robertson-Wilson, Lisa Wood and Ran Falconer -- Understanding the local physical activity environment and obesity / Gavin Turrell -- Childhood obesity, physical activity, and the physical environment / Melody Oliver and Grant Schofield -- Policy responses and obesogenic food environments / Katrina Giskes -- Policy responses and the physical environment / Mylene Riva and Sarah Curtis -- Residential environments and obesity : estimating causal effects / Graham Moon -- Measuring obesogenic environments : representing place in studies of obesity / Dianna Smith, Kim Edwards, Graham Clarke and Kirk Harland -- Recourse to discourse : talk and text as avenues to understand environments of obesity / Robin Kearns -- Conclusions : common themes and emerging questions / Jamie Pearce and Karen Witten.
Includes bibliographical references and index.
Keywords: Obesity -- Epidemiology; Obesity -- Prevention; Obesity -- epidemiology; Obesity -- prevention & control; Environment; Risk Factors; World Health